The Gift of a Vocation: Learning, Writing, and Teaching Sociology - Kleinman, Sherryl (Qualitative Sociology Review, 2020)
To write a sociological festschrift for a scholar necessarily means looking at a chain of influence instead of one person. In this essay, I honor William Shaffir, Emeritus Professor of Sociology at McMaster University, who taught me as I worked towards the MA. I examine what I learned from him by starting with my undergraduate experiences at McGill University, where Billy (I never heard anyone call him William) received his PhD. We shared influences there, including those who had studied with Howard S. Becker at Northwestern University. I then turn to my time at McMaster, and how Billy strengthened my knowledge of symbolic interactionism and qualitative methods, as well as taught me important lessons about writing. He also reduced graduate students’ anxieties, including mine, through two words: “No problem.” My experiences with Billy provided a model of mentoring that challenged the usual hierarchy between graduate students and professors. Those lessons were reinforced as I pursued a PhD at the University of Minnesota and spent two quarters at Northwestern University as a visiting student. These connecting influences helped me write and teach sociology in a largely quantitative department at the University of North Carolina-Chapel Hill, where I lacked the kind of support I had received as an undergraduate and graduate student. I taught there over 37 years, practicing the kind of sociology and mentoring that Billy generously modeled so many years ago.